2017
DOI: 10.1016/j.jtcme.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of curcuminoids, other biomolecules from turmeric and their derivatives – A review

Abstract: In recent years, several drugs have been developed deriving from traditional products and current drug research is actively investigating the possible therapeutic roles of many Ayruvedic and Traditional Indian medicinal therapies. Among those being investigated is Turmeric. Its most important active ingredient is curcuminoids. Curcuminoids are phenolic compounds commonly used as a spice, pigment and additive also utilized as a therapeutic agent used in several foods. Comprehensive research over the last centur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
413
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 730 publications
(480 citation statements)
references
References 160 publications
12
413
1
8
Order By: Relevance
“…As can be seen, the antioxidant potential of single curcuminoids is higher than curcuminoids in complexes with cyclodextrin and phospholipid, respectively. The antioxidant mechanism of curcumin was explained by the density functional theory with five different mechanisms including single electron transfer, radical adduct formation, H atom transfer from neutral curcumin, H atom transfer from deprotonated curcumin and sequential proton loss electron transfer (Amalraj et al, 2016). In our study, we did not observed an increase in the antioxidant activity of curcumin in complexes.…”
Section: Abts Radical Scavenging Methods Is Based On the Reduction Ofcontrasting
confidence: 50%
“…As can be seen, the antioxidant potential of single curcuminoids is higher than curcuminoids in complexes with cyclodextrin and phospholipid, respectively. The antioxidant mechanism of curcumin was explained by the density functional theory with five different mechanisms including single electron transfer, radical adduct formation, H atom transfer from neutral curcumin, H atom transfer from deprotonated curcumin and sequential proton loss electron transfer (Amalraj et al, 2016). In our study, we did not observed an increase in the antioxidant activity of curcumin in complexes.…”
Section: Abts Radical Scavenging Methods Is Based On the Reduction Ofcontrasting
confidence: 50%
“…Nanoparticles containing antimicrobial and antioxidant substances could be considered as a new trend of antimicrobial therapeutic agents for the prevention and reduction of deterioration of food and pathogenic microorganisms [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Curcuma aeruginosa RoxB. is a medicinal plant that contains phytochemical phenolic, flavonoid (Waras Nurcholis, Khumaida, Syukur, & Bintang, 2016b) and curcuminoids (Bos et al, 2007;Waras Nurcholis, Khumaida, Syukur, & Bintang, 2016a), so it's a potential source of natural antioxidant (Amalraj, Pius, Gopi, & Gopi, 2017;W Nurcholis, Khumaida, Syukur, Bintang, & Ardyani, 2015). C. aeruginosa has a broad geographical scope in Indonesia, which necessitates extensive investigation on the antioxidant attributes of their different accessions.…”
Section: Introductionmentioning
confidence: 99%